Exceptional sets in homogeneous spaces and hausdorff dimension - Kadyrov, Shirali (My University, 2015)
In this paper we study the dimension of a family of sets arising in open dynamics. We use exponential mixing results for diagonalizable ows in compact homogeneous spaces X to show that the Hausdorff dimension of set of points that lie on trajectories missing a particular open ball of radius r is at most dimX + C rdimX log r; where C > 0 is a constant independent of r > 0. Meanwhile, we also describe a general method for computing the least cardinality of open covers of dynamical sets using volume estimates.
Keywords: Mathematics; Hausdorff dimension